PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN ORANG DI WILAYAH HUKUM POLDA LAMPUNG - nurbaiti syarif (Jurnal Pro Justitia (JPJ), 2020)
ABSTRACT The social phenomenon that occurs today still encountered cases related to the crime of trafficking in the Legal Territory of Lampung Police. Problems in this research are: How the application of criminal sanctions against perpetrators of trafficking in persons in the Legal Territory of Lampung Police. What is the law enforcement effort in handling the criminal acts of trafficking in the Legal Territory of Lampung Police. Based on the results of research and discussion shows that the application of criminal sanctions against perpetrators of trafficking in persons in the Legal Territory of Lampung Police conducted by arrest by Ditreskrimum Lampung Police against the suspects committed criminal acts as the fulfillment of material elements in Law Number 21 Year 2007 on Eradication Criminal Acts of Trafficking in Persons, Legal proceedings carried out by Police investigators of Lampung to court stage with the achievement of Court Decision with the sentence of imprisonment and fine to the Defendant. The form of the application of criminal sanctions is based on errors that comply with the elements of the law and there is no reason for the elimination of the unlawful nature of the action, the deliberate element by the perpetrator (dolus) so there is no justification or excuses for him to avoid punishment. Law enforcement efforts in combating trafficking of persons in the Legal Territory of Lampung Police are carried out using non-penal means and penal means. The non-penal approach is carried out by counseling, social education in order to develop the social responsibility of citizens aware of the crime of trafficking in persons, legal counseling, resocialization, workshops, etc., especially in environments prone to crime, handling crime objects. Penal Approach is done by legal effort that perpetrator of criminal trafficking of people is processed by law based on the provisions of legislation up to court level and execution in order to get criminal sanction and guarantee legal certainty in society.Keywords: Implementation, Sanctions, Criminal Acts, Trafficking